The determinants of the financial derivatives' usage within SME businesses in Pakistan - Nawaz, Muhammad (2018)
The usage of financial derivatives has been recognized in improving the financial performance of an organization. However, few studies have explored the usage of financial derivatives within small and medium enterprises (SMEs) particularly within SMEs in Pakistan. This gap provides the impetus for this research to establish the determinants of financial derivatives’ usage by SMEs in Pakistan. This research was guided by the following research problem: ‘how and why the determinants of the financial derivatives’ usage could be established within SMEs in Pakistan?’ A qualitative study using the convergent interview method was conducted to investigate the research issues. The interviewees were identified using the purposive-snowballing sampling technique. Nineteen (19) convergent interviews were conducted to confirm the determinants of financial derivatives’ usage. The thematic analysis technique was used to analyze the data. The research findings confirmed a total of twenty four (24) determinants of financial derivatives’ usage. Five of these determinants, namely, time horizon, un-invested cash, reduction in overall cost, risk appetite, and lack of established markets are newly emerging determinants and contribute to the body of knowledge. In addition, six (6) core and six (6) non-core financial determinants are confirmed. Also, two (2) core and ten (10) non-core non-financial determinants are confirmed. This research provides two theoretical implications, generating new knowledge for theory building and contributing to existing knowledge in terms of the newly emerging determinants. The methodological implications include the power of using qualitative convergent interviews and the snowball sampling technique. The practical implications include guidelines to the Chief Financial Officers (CFOs) to optimize the utilization of financial derivatives within SMEs in Pakistan. Finally, this research provides policy implications for government authorities and agencies in formulating the regulations and procedures for the usage of financial derivatives by the SMEs in Pakistan.